The Effect of Competence, Motivation, and Organizational Culture on Employee Performance - Hifny, Muhammad; Hermawan, Rangga Adhitia; Hidayat, Wahyu (Lensa Ilmiah: Jurnal Manajemen dan Sumberdaya, 2026)
This study examines the associations between competence, work motivation, organizational culture, and employee performance at PT Esefa Semesta Facility, a facility services company characterized by strict adherence to standard operating procedures, consistent field service delivery, and responsiveness to client demands. The study employed a quantitative explanatory cross-sectional design using a structured questionnaire distributed to all employees through saturated sampling (n = 62). Data were analyzed using multiple linear regression in SPSS 26 following instrument validity, reliability, and classical assumption testing. The findings indicate that competence (B = 0.331; p = 0.010), work motivation (B = 0.284; p = 0.020), and organizational culture (B = 0.388; p = 0.010) are positively and significantly associated with employee performance. Simultaneously, the regression model is statistically significant (F = 102.080; p < 0.001) and demonstrates substantial explanatory power (Adjusted R² = 0.833), indicating that 83.3% of the variance in employee performance is explained by the three predictors. These results suggest that enhancing job-relevant competencies, maintaining sustainable work motivation, and fostering an adaptive organizational culture constitute practical managerial levers for minimizing service variability and strengthening performance in facility service operations. However, causal interpretation should be made cautiously due to the cross-sectional nature of the study design.